Lands and peoples. The world in color. Volume 1 : british isles, western Europe - Merrick, Helen Hynson
Great Britain -- England -- London -- Wales -- Scotland -- Ireland -- Atlantic islands -- The Netherlands -- Belgium -- France -- Normandy and Brittany -- Paris -- Spain -- Portugal -- Mediterranean islands